A Treinabilidade da Atenção na Prática Esportiva: uma abordagem com goleiros de futebol de campo. - Silva Junior, Milton Gomes da (2006)
Any form of attention is continuously present in the human conscious activity, bringing implications and interests for both the clinical and Health Psychology areas. Attention is seen as a selective, intensive and directed state of perception. Within the sports context, there is much of attention field to be explored. The goal of this work was to test the goalkeepers attention by means of two experimental tasks. Our hypothesis was that the sports practice, specifically in goalkeepers because of their training, enhances their performance in tasks apart from the peculiar concept of the sport. What is more: it provides a performance enhancement, if it is due to the perceptive component of discrimination, to the temporal placement of attention or to the attention s maintenance for extended periods; in other words, it provides a higher capacity of concentration and less fatigability. We compared 27 soccer goalkeepers, between the ages of 15 and 27, divided by their time of practice. In this study, we used a computer commercial program, configured to the creation of attention tests (Stim, Neurosoft. Inc.), which controls all of aspects of the task. We correlated the reaction time and the percentage of rights with the length of the goalkeeping raining in months (along with the age). We divided the group of goalkeepers into two subgroups by means of the training time median. Despite the high correlation between training time and age, in our sample there was no significant correlation between age and performance in both of the tasks. The correlation between performance and training time was highly significant on task I. we did not verify the correlation between performance and training time on tasks II, despite the significant correlation between the performance on the two tasks. Correlation analyses between training time and performance were carried out on the tasks, separated by blocks. On task I, the correlation between training time and performance in each block was always significant; both in the parametric and non-parametric test. On task II, however, there was no significant correlation between training time and performance in any of the blocks. In the categorical analysis, which is an analysis of the two groups that were divided into two subgroups by means of the training time median, the difference in performance between the subgroups was significant only on task I, in the total sum of rights (T-test of independent samples; F=4.36, p=0.037) and in the rights within the two blocks (block 3 p=0.048; block 4 p=0.026). With training time, the enhancement of what differs them and the increase in fatigability condition tend to refine and reduce. The sports practice can indeed enhance the perceptive capacity and the attention s maintenance, which is the basis of the human discipline for the achievement of any task. Consequently, an affective and somatic increase, besides a cognitive intellectual increase, brings a real applicability in people s quality of life